1984
DOI: 10.1083/jcb.99.1.222s
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between glycolytic enzymes and components of the cytomatrix.

Abstract: Evidence is provided that enzymes absorb to cellular structures in a wide range of tissues . In particular, the interactions between glycolytic enzymes and the microfilaments of the cytoplasm are described . The relevance of these interactions to the compartmentation of carbohydrate metabolism is discussed . Examples are given of the variations in degree of binding during alteration of tissue metabolism and, for individual glycolytic enzymes, during fetal development and differentiation . Overall, these data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(82 citation statements)
references
References 19 publications
5
77
0
Order By: Relevance
“…A stably polymerized form of actin has been identified in the axon (48). Furthermore, microfilaments bind many different cytoplasmic proteins, including metabolic enzymes such as aldolase, with relatively high affinity (41). Thus, microfilaments could provide a large number of sites for binding other SCb proteins to the carrier structure .…”
Section: Identification Of the Proteins Comprising The Carrier Structmentioning
confidence: 99%
“…A stably polymerized form of actin has been identified in the axon (48). Furthermore, microfilaments bind many different cytoplasmic proteins, including metabolic enzymes such as aldolase, with relatively high affinity (41). Thus, microfilaments could provide a large number of sites for binding other SCb proteins to the carrier structure .…”
Section: Identification Of the Proteins Comprising The Carrier Structmentioning
confidence: 99%
“…Numerous studies have demonstrated interactions between the cytoskeleton and glycolytic enzymes, especially GAPDH, aldolase and PK. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] In this study, quantities of these glycolytic enzymes, as well as actin, tubulin and tropomyosin, were sufficient in U87 pseudopodia to be detected with Figure 4 DeCyder ratios Coomassie blue staining, thus establishing the potential for the energy-generating portion of the glycolytic pathway to energize cytoskeletal proteins for migration within U87 pseudopodia. Polymerization of actin and tubulin shares a similar use of energy from nucleotide triphosphate hydrolysis.…”
mentioning
confidence: 96%
“…This work suggested that previously reported "glycolytic component" complexes (13,14,34) were actually complexes of glycolytic enzymes with structural proteins, and implied that the glycolytic particle might exist as such a complex. The model for the cytoplasmic organization of glycolytic enzymes that has emerged from Clarke and Masters' work is that there is a "plating" of glycolytic enzymes around the filamentous actin (F-actin) ~ core of microfilaments (48). Masters proposed a dynamic three-way equilibrium among monomeric actin, F-actin, and glycolytic enzymes, resulting in a microdomain of glycolytic enzymes surrounding actin filaments.…”
mentioning
confidence: 99%